2014
DOI: 10.1186/1748-7161-9-s1-o5
|View full text |Cite
|
Sign up to set email alerts
|

Rasterstereography a reliable tool in scoliosis measurement – a critical review of literature

Abstract: Measuring the structural deformities of the spine is always a challenge for the clinician, since it is important to make clinical decision. When repeated exposure to the X ray has to be reduced in the routine practice, rehabilitation professionals are looking for a tool to be used in daily practice. Rasterstereography is one such method used from the early of 1980s attracted the attention of clinician in the western world. Recently it has been introduced to the developing countries like India. In this context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Patikimiausias būdas diagnozuoti ir sekti tolesnius stuburo linkių pokyčius esant IS yra tyrimas rentgenu. Atlikta nemažai studijų apie paviršiaus topografijos tyrimo patikimumą diagnozuojant ir stebint skoliozę (Swaminathan et al, 2014). Paviršiaus topografija yra gaunami objektyvūs stuburo rotacijos rezultatai, ir šis būdas gali būti alternatyva tradiciniams stuburo rotacijos vertinimo metodams (Hackenberg et al, 2006).…”
Section: įVadasunclassified
“…Patikimiausias būdas diagnozuoti ir sekti tolesnius stuburo linkių pokyčius esant IS yra tyrimas rentgenu. Atlikta nemažai studijų apie paviršiaus topografijos tyrimo patikimumą diagnozuojant ir stebint skoliozę (Swaminathan et al, 2014). Paviršiaus topografija yra gaunami objektyvūs stuburo rotacijos rezultatai, ir šis būdas gali būti alternatyva tradiciniams stuburo rotacijos vertinimo metodams (Hackenberg et al, 2006).…”
Section: įVadasunclassified
“…Among several commercial systems, the Formetric-4D system (Diers International GmbH, Schlangenbad, Germany) has been validated against 2D radiography by a collaborative study between the Diers company and German universities [23]. This system is largely used in research to measure and control spine deformities in AIS patients [26][27][28][29][30][31]. Most of the previous studies evaluating the validity of this system [31] concluded a good to strong correlation (r > 0.60) compared with 2D radiographs.…”
Section: Introductionmentioning
confidence: 99%